THE INFLUENCE OF SOCIAL MEDIA ON THE MENTAL HEALTH OF GEN Z EMPLOYEES IN INDONESIA - Rieneke Ryke Kalalo; Irwan Amar; Silviani Joice Lengah; Ridwan; Cakra Zaitun (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This research is a quantitative research with an explanatory approach. The data used in this article is primary data that researchers obtained directly through online questionnaires. The data obtained was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the hypothesis in this study is that the Social Media variable can have a positive relationship direction and a significant influence on Mental Health. This is because the P-Values ​​are positive and below the significance level of 0.05, namely 0.008These results are because social media can facilitate existing work, reduce employee workload, as a medium of entertainment, and ultimately improve employee Mental Health. Thus it can be concluded that the hypothesis in this article can be proven.